1995
DOI: 10.1007/bf00020399
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar properties of the PsaF photosystem I protein from the green alga Chlamydomonas reinhardtii: presequence independent import of the PsaF protein into both chloroplasts and mitochondria

Abstract: It has previously been shown that presequences of nuclear-encoded chloroplast proteins from the green alga Chlamydomonas reinhardtii contain a region that may form an amphiphilic alpha-helix, a structure characteristic of mitochondrial presequences. We have tested two precursors of chloroplast proteins (the PsaF and PsaK photosystem I subunits) from C. reinhardtii for the ability to be imported into spinach leaf mitochondria in vitro. Both precursors bound to spinach mitochondria. The PsaF protein was converte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 32 publications
(45 reference statements)
0
7
0
1
Order By: Relevance
“…[38][39][40] However, it has also been shown that some chloroplast proteins can be mistargeted to mitochondria in vitro, 10,39 whereas no mistargeting of mitochondrial proteins to chloroplasts has been observed. In order to avoid mistargeting of chloroplast proteins to mitochondria in vitro, we have developed a dual import system in which the precursor protein is incubated with a mixture of isolated mitochondria and chloroplasts followed by reisolation of the organelles.…”
Section: Import Of Aars-gfp Fusion Constructs Into Mitochondria and Cmentioning
confidence: 95%
“…[38][39][40] However, it has also been shown that some chloroplast proteins can be mistargeted to mitochondria in vitro, 10,39 whereas no mistargeting of mitochondrial proteins to chloroplasts has been observed. In order to avoid mistargeting of chloroplast proteins to mitochondria in vitro, we have developed a dual import system in which the precursor protein is incubated with a mixture of isolated mitochondria and chloroplasts followed by reisolation of the organelles.…”
Section: Import Of Aars-gfp Fusion Constructs Into Mitochondria and Cmentioning
confidence: 95%
“…To determine how proteins are targeted to the organelles in C. reinhardtii, it is important to study directly the import of precursor proteins into C. reinhardtii organelles. We have recently initiated such studies [27] and further experiments are in progress.…”
Section: N-terminal Sequencesmentioning
confidence: 99%
“…The mitochondrial pre‐sequence of the yeast cytochrome oxidase subunit Va can function both as a mitochondrial and chloroplastic targeting peptide in transgenic tobacco (Huang et al ., 1990). The PsaF protein from C. reinhardtii was shown to be imported in vitro into spinach and C. reinhardtii mitochondria (Hugosson et al ., 1995). The transit peptides of the chloroplast outer envelope proteins, triose‐3‐phosphoglycerate phosphate translocator (TPT) and the 37 kDa protein coupled to CAT were imported into plant mitochondria in vitro but not in vivo (Brink et al ., 1994; Silva Filho et al ., 1997).…”
Section: Introductionmentioning
confidence: 99%